Using inductive machine learning to identify risk factors for healthcare workers to get infected with highly contagious viruses (based on COVID-19 model) - I.A. Egorov; S.S. Smirnova; A.V. Semenov (Analiz Riska Zdorovʹû)
Epidemic and pandemic spread of highly contagious viruses (SARS-CoV, influenza A virus, Ebola virus, MERS-CoV, and SARS-CoV-2) has been a trend observed in the first two decades of the 21st century.